Reconceptualizing social inclusion in social enterprises: The case of work integration social enterprises in Vietnam - Cao, Oanh Tu; Nguyen, Quy Ngoc; Pham, Thang Vu (Edelweiss Applied Science and Technology, 2025)
Social enterprises are increasingly recognized as key actors in fostering social inclusion, particularly through work-integration initiatives that support marginalized populations. However, the mechanisms through which social inclusion is created remain contextually underexplored. This study draws on qualitative data from Work Integration Social Enterprises (WISEs) in Vietnam to investigate the processes through which social inclusion is created and to refine its conceptualization. Primary data were obtained from semi-structured interviews conducted with the business owners of 15 WISEs. Findings show that while access to employment is crucial, deeper inclusion occurs through participation in social and organizational life, and through the personal empowerment of disadvantaged individuals. The Vietnamese context reveals distinctive pathways to inclusion, influenced by strong cultural values such as family ties and empathy-driven leadership, often shaped by founders’ own experiences of marginalization. Based on these insights, the paper proposes a three-tier framework of social inclusion impact, grounded in theory and enriched by empirical evidence. This framework not only enhances understanding of inclusion in developing contexts but also offers a foundation for further comparative research. The study contributes to the evolving theory of social entrepreneurship by clarifying the mechanisms through which inclusion is achieved and provides practical implications for designing inclusive enterprises and policies in resource-constrained environments.